2014
DOI: 10.1080/10426914.2014.962660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystallographic Anisotropy on Micro EDM Process

Abstract: In this paper, experiments are conducted by machining from different crystallographic orientations of monocrystalline silicon, and the effects of crystallographic orientation on the micro electrical discharge machining (EDM) process are discussed. The results demonstrate that the machining speed and surface roughness are varied when crystallographic orientation changes. The surface roughness is seen to vary by as much as twofold with crystallographic orientation, while the ratio between the maximum and minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…XRD patterns and SEM microstructure images of wrought and LPBF-IN718 samples are presented in Figure 2 2). Note that the electrical and thermal conductivities of the material, which affect machinability, are altered by the grain size, grain boundary, and grain orientation, thus, microstructural characteristics of the samples are critical for determining the machining performance [29,[33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD patterns and SEM microstructure images of wrought and LPBF-IN718 samples are presented in Figure 2 2). Note that the electrical and thermal conductivities of the material, which affect machinability, are altered by the grain size, grain boundary, and grain orientation, thus, microstructural characteristics of the samples are critical for determining the machining performance [29,[33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that crystallographic orientation control for LPBF-fabricated samples can enhance the structural and functional properties of materials [8,9,40]. Besides, the in uence of crystallographic anisotropy on the WEDM performance of monocrystalline Si has been studied [34], discussing variations of WEDM performance (MRR and roughness) depending on the crystallographic orientation. In this reference study, (100)-oriented Si displayed different MRR and surface roughness with changes in machining direction because of different physical characteristics of the crystal orientations.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of preheated boron carbide (5 wt%) and SiC (5 wt%) reinforcement to aluminium 6351 by the stir casting process improved the ultimate tensile strength, yield strength, and scratch-resisting capacity of the alloy. 7 Further, increasing the weight-wise % of B 4 C to 10 wt% along with 5 wt% SiC has a 10.10% increase in tensile strength, 8.78% increase in yield strength, 7.26% increase in hardness, and a very marginal decrease in density. 8 Dhoria et al conducted a comprehensive analysis by fabricating a hybrid metal matrix composite of AA6351 using different proportions of Gr and SiC employing a squeeze casting process.…”
mentioning
confidence: 94%
“…mechanical or functional properties offers possibilities for a diverse range of applications [1][2][3][4][5][6][7]. In particular, metallic miniature parts already find applications in high sensitive temperature transducers and pressure sensors, high precision resistors and capacitors, wearable biomedical devices and ultra high speed inkjet printers.…”
mentioning
confidence: 99%
“…In order to improve the precision, combined techniques involving the photolithography and soft lithography offers a feasible alternative. The main advantage of the photolithography over other techniques is that much higher precision can be achieved and high quality microstructures can be fabricated during the process [2]. Meanwhile, the soft lithography allows the production of the replicas of the mould with fine features.…”
mentioning
confidence: 99%